ANALISIS PENGGUNAAN APLIKASI MERDEKA MENGAJAR TERHADAP PEMAHAMAN GURU TERKAIT IMPLEMENTASI KURIKULUM MERDEKA - Dedy Setyawan; Syamsuryawati Syamsuryawati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The purpose of this study was to find out how teachers at SMA Hang Tuah Makassar build an understanding of the implementation of the independent curriculum through the independent teaching application. The design of this study is explorative, namely exploring and describing in-depth information about a phenomenon. The results of the study refer to the test of understanding the implementation of the free curriculum showing that subjects A and C are in the very good category while subject B is in the good category, this is because subject B, although he has completed independent training, is no longer studied regularly, while subject D has not fully completed independent training on the independent teaching app. The results of the research referring to the results of learning observations and the completeness of learning tools show that subjects A, B, and C carry out all the stages/steps of learning contained in the learning module even though there are some that are mixed up due to the situation and condition of the students and the learning process has been set for students and the teacher as a facilitator and fun learning. While subject D has not shown the learning that is learned by students, the active participation of teachers and students still looks the same and has not functioned as a facilitator as a whole and there are several learning steps that have not been carried out such as giving trigger questions and reflections that are not appropriate. The results of the interviews showed that subjects A and C completed periodic self-training, then subject B completed independent training in a short period of time and after that was no longer studied regularly. While subject D has not completed independent training and also has not studied it regularly.